English Learning Needs of Sport Students: Toward a Project-Based Approach with 4C Skills - Sari, Mike Nurmalia; Zaim, M.; Ardi, Havid (UNIB Press, 2025)
Studies on English language learning practices in Sport have received considerable interest from scholars in recent years due to the significance of English skills for graduates in the job market and professional settings. However, there is limited research that has focused on investigating the needs of Sport students in learning English through effective pedagogical approaches that integrate Project-based Learning (PjBL) with 4C skills: Critical Thinking, Communication, Collaboration, and Creativity. This study aims to 1) investigate the specific English learning needs of Sport students in higher education, and 2) examine preferred learning approaches that integrate PjBL with 4C skills. This exploratory sequential mixed-methods design combined quantitative data from structured questionnaires with qualitative insights from interviews, involving 52 sport students (30 males and 22 females) at a higher education institution in Sungai Penuh, Jambi, Indonesia. The findings reveal that sports students require proficiency in listening, speaking, reading, writing, vocabulary, and grammar, with a particular emphasis on sports-specific terminology and contexts. Furthermore, the qualitative results indicate that students strongly favor learning approaches that are collaborative, authentic, and project-based. They perceive Project-Based Learning (PBL) as highly effective, particularly when it promotes 4C skills. Students expressed those tasks such as video creation, podcast production, simulations, and team discussions enhance their engagement, confidence, and practical language use. These findings suggest that integrating PjBL with 4C skills into English instruction is essential for meeting the specific language needs of sports students and enhancing their readiness for global professional environments.